Dualistic distribution coefficients of elements in the system mineral-hydrothermal solution. I. Gold accumulation in pyrite - Tauson V.L.; Babkin D.N.; Pastushkova T.M.; Krasnoshchekova T.S.; Lustenberg E.E.; Belozerova O.Yu. (My University, 2011)
The use of trace elements (TE) as geochemical indicators is complicated by the dualism of their distribution coefficients D due to the additional (i.e., above the concentrations of an isomorphic component) incorporation of elements at structural defects of various nature (including the surface of the crystal). A pressing problem in this situation is to determine the true D values that pertain to the structural component of an admixture D str and evaluate effects of other modes of TE occurrence. Only upon distinguishing D str in the bulk coefficient D bulk it is possible to evaluate the ore potential of fluid in terms of certain TE from the composition of a mineral containing the TE. Pyrite synthesized in solutions of variable pH at 450°C and 1 kbar (100 MPa) at fluid portions sampled in a trap is utilized to demonstrate the role of a surface nonautonomous phase (NP) in the incorporation of gold in this mineral. The distribution coefficient of gold between pyrite and hydrothermal solution is 0.14 for “pure” pyrite and 0.05 for As-bearing pyrite (containing 0.02–0.05 wt % As), and these coefficients for NP are 310 and 170, respectively. This increases the D bulk for evenly distributed (“invisible”) gold by factors of four and nine. In contrast to the results of earlier studies conducted at room temperature and pressure or parameters close to them, our data demonstrate that the accumulation of “invisible” Au in pyrite is controlled not only by reducing adsorption with the development of Au(0) particles and films but also by Au incorporation in NP developing in the surface layer of the crystal approximately 500 nm thick as chemically bound Au [most likely as Au(I)]. The possible reason for the high absorption capacity of NP is the defect (pyrrhotite-like) structure, which is not saturated with bonds of excess S and sulfoxi onions.
Keywords: pyrite; gold